TEACHER SELF-LEADERSHIP IN THE INTEGRATION OF DIFFERENTIATED LEARNING AND DEEP LEARNING AT SMA XAVERIUS BANDAR LAMPUNG - Resti Hosiana Situmorang; Susanto Susanto (PT. Saha Kreasi Indonesia, 2026)
This study aims to analyze teacher self-leadership in integrating differentiated instruction and deep learning at SMA Xaverius Bandar Lampung. This study employed a descriptive qualitative approach. The participants consisted of ten teachers, one vice principal for curriculum, and one principal. Data were collected through classroom observations, interviews, and documentation. Data validity was established using source triangulation and technique triangulation. Data were analyzed through the stages of understanding (verstehen), interpretation, coherence, hermeneutics, and inductive analysis. The findings indicate that teachers have demonstrated self-leadership through self-management, self-reflection, professional development, instructional initiative, and adaptability. Differentiated instruction and deep learning have been implemented, although several aspects still require improvement. Supporting factors include teachers’ commitment, school leadership, collaborative culture, and learning facilities, while the main challenges are limited instructional time, diverse student characteristics, teachers’ workload, and varying digital competencies. The study concludes that teacher self-leadership plays an important role in supporting the integration of differentiated instruction and deep learning to create student-centered learning.